2015
DOI: 10.1039/c5cc06370a
|View full text |Cite
|
Sign up to set email alerts
|

Low charge overpotentials in lithium–oxygen batteries based on tetraglyme electrolytes with a limited amount of water

Abstract: High charge overpotentials are a great challenge for the realization of lithium-oxygen batteries. Here, we construct a Li-O2 battery system by introducing a limited amount of water into tetraglyme based electrolytes and electrolytic MnO2 (EMD) and Ru supported on Super P as cathodes for Li-O2 batteries. This results in low charge potentials of around 3.2 V, corresponding to overpotentials of 0.24 V, and outstanding rate capability and cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 42 publications
4
83
0
2
Order By: Relevance
“…This is the reason why a trace amount of water in electrolytes can catalyze the reactions on the cathode of Li–air batteries during discharge and charge, thereby resulting in increased capacity . The charge overpotentials and the morphologies of the discharge products depend on the H 2 O concentration in the electrolyte (Figure f–j) . If an excess amount of H 2 O is present in the electrolyte, the discharge product will be disk‐shaped LiOH instead of the typical toroidal‐shaped Li 2 O 2 .…”
Section: Aprotic Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the reason why a trace amount of water in electrolytes can catalyze the reactions on the cathode of Li–air batteries during discharge and charge, thereby resulting in increased capacity . The charge overpotentials and the morphologies of the discharge products depend on the H 2 O concentration in the electrolyte (Figure f–j) . If an excess amount of H 2 O is present in the electrolyte, the discharge product will be disk‐shaped LiOH instead of the typical toroidal‐shaped Li 2 O 2 .…”
Section: Aprotic Electrolytesmentioning
confidence: 99%
“…j) Evolution of the morphology of discharge products in different H 2 O‐containing electrolytes. Reprinted with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Aprotic Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of electrochemical catalysis, the defects are considered to be good catalytic sites for the electrochemical reaction with oxygen. Because of its unique structural characteristics, γ‐MnO 2 is a promising oxygen catalyst and has been widely used as cathodic catalyst of Li–O 2 battery . According to the different preparation methods, γ‐phase MnO 2 can be divided into CMD and EMD.…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 99%
“…In other words, the electrochemical reaction is only partially reversible. To solve these problems, Zhou and co‐workers studied the effect of water on the electrochemical processes of EMD‐catalyzed Li–O 2 batteries in detail, and demonstrated that dimethyl sulfoxide (DMSO) and tetraglyme (G4) containing trace water could match well with an EMD/Ru/Super P carbon cathode. Using this system, the overpotential was reduced to ≈0.21 V at 500 mA g −1 , and superior rate performance and cycling stability were obtained ( Figure a,b).…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 99%